2017
DOI: 10.2174/1573397112666160331142548
|View full text |Cite
|
Sign up to set email alerts
|

Weight Bearing Joints Destruction In Rheumatoid Arthritis

Abstract: In many cases of rheumatoid arthritis (RA) joints of the upper extremities are affected. However, involvement of weight bearing joints of the lower extremities is strongly associated with a decreased activities of daily living ability such as gait disorder. Once the progression of weight bearing joint destruction occurs, lower extremity function will decrease even if RA disease activity is improved by pharmacotherapy. In this article, we investigated joint destruction suppressing effects of pharmacotherapy on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…RA commonly affects the hip joint and is a potential etiology of end-stage arthrosis [1,4,18]. Imagama, et al reported that RA can lead to joint destruction, decreased activities of daily living, and gait disorder [19]. Often THA is the treatment for those with debilitating hip pain, arthrosis and destruction by RA [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…RA commonly affects the hip joint and is a potential etiology of end-stage arthrosis [1,4,18]. Imagama, et al reported that RA can lead to joint destruction, decreased activities of daily living, and gait disorder [19]. Often THA is the treatment for those with debilitating hip pain, arthrosis and destruction by RA [6,20].…”
Section: Discussionmentioning
confidence: 99%
“…In general, these processes occur in the small joints of the feet and hands but may also occur in larger joints such as the shoulder and knees. [65][66][67][68][69][70] These symptoms are more pronounced after long periods of inactivity, and a conspicuous feature of the disease is increased stiffness in the morning. [71][72][73][74][75] Pain related to RA is caused at the inflammation site and is classified as nociceptive rather than neuropathic.…”
Section: Risk Factors and Symptomsmentioning
confidence: 99%
“…In contrast to patients with osteoarthritis with impairment of one knee, rheumatics involve several joints of the lower extremities in the disease process. Pain and arthritic changes in the pelvis and ipsilateral hip lead to changes in the kinematics of the knee joint, as do deformities of the hindfoot as a result of posticus insufficiency [29][30][31][32]. The supposedly well-intentioned protection impairs the overall mobility of patients in the long term.…”
Section: Biomechanics and Clinic Of The Rheumatic Kneementioning
confidence: 99%